2022
DOI: 10.1183/23120541.00350-2022
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary rehabilitation in intensive care for COVID-19: randomised controlled trial

Abstract: The coronavirus disease 2019 (COVID-19) has led to an increasing number of patients in the intensive care units (ICU). The size of this post-ICU cohort will be unprecedented, with many patients vulnerable to post-intensive care syndrome. We analysed the respiratory and functional effects of a multidisciplinary rehabilitation program on functional performance, in patients hospitalized in ICU due to COVID-19.We conducted a randomized controlled clinical trial. Ninety-six patients, who fulfilled the eligible crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…Exercise capacity outcomes, including the Six-Minute Walk Test (6MWD) and the Sit-To-Stand Test (STS), were synthesized from data obtained in 16 RCTs. Out of these, 12 RCTs 31,[43][44][45][46][47]49,54,56,60,61,63,64 assessed 6MWD, revealing moderate-level evidence of improved walking outcomes in patients who underwent rehabilitation interventions compared to those receiving standard care (MD 38.18 [25.33, 51.03], I² = 88%) (Figure 4). Subgroup analysis by delivery mode indicated that tele-rehabilitation (MD 66.89 [32.15, 101.62], I² = 90%) appeared more effective than in-person rehabilitation 93.21], I² = 92%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise capacity outcomes, including the Six-Minute Walk Test (6MWD) and the Sit-To-Stand Test (STS), were synthesized from data obtained in 16 RCTs. Out of these, 12 RCTs 31,[43][44][45][46][47]49,54,56,60,61,63,64 assessed 6MWD, revealing moderate-level evidence of improved walking outcomes in patients who underwent rehabilitation interventions compared to those receiving standard care (MD 38.18 [25.33, 51.03], I² = 88%) (Figure 4). Subgroup analysis by delivery mode indicated that tele-rehabilitation (MD 66.89 [32.15, 101.62], I² = 90%) appeared more effective than in-person rehabilitation 93.21], I² = 92%).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies 38,51,[59][60][61]85,87,91,94,[99][100][101] reported length of ICU or hospital stay (LOS) for patients. Among them, eight studies 38,[59][60][61]85,87,94,100 did not demonstrate a shorter average LOS following rehabilitation interventions. This may be due to the inclusion of older patients (over 65 years) compared to studies with positive outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6MWT is a functional performance test previously used in the follow-up of COVID-19 ( 40 , 41 ). Our results indicate a moderate reduction in distance and oxygen saturation, which could be related to the severity of lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…A melhora dessas condições contribui com a recuperação da qualidade de vida dos pacientes e o reflexo da reabilitação, incide nos índices de vigilância em saúde, diminui o impacto negativo na vida das pessoas e nas atividades econômicas. [18][19][20][21]…”
Section: Introductionunclassified